ANALISIS KUALITAS BUTIR SOAL ASESMEN TENGAH SEMESTER GENAP MATA PELAJARAN MATEMATIKA KURIKULUM MERDEKA KELAS VII SMP NEGERI 2 KURIPAN TAHUN AJARAN 2024/2025 - Syufa Auliya, Annisa; Hikmah, Nurul; Yulis Tyaningsih, Ratna; Turmuzi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the quality of even midterm assessment items in the mathematics subject of the Merdeka Curriculum for Class VII of SMP Negeri 2 Kuripan in the 2024/2025 academic year in terms of suitability of questions with grids, validity, reliability, difficulty level, differentiating power, and effectiveness of checkers. The method used is Mixed Method with descriptive qualitative and quantitative approaches. The data obtained will be analyzed using the SPSS version 27 program and the Microsoft Excel program. The results of the qualitative analysis of the research show that: 30 out of 30 items or 100% of the questions are in accordance with the grid from the material aspect, construction aspect, and language aspect. The results of the quantitative analysis of the study showed that: (1) valid questions amounted to 28 items (93.33%), and invalid questions amounted to (6.67%); (2), the question has high reliability with a coefficient of 0.816; (3) Based on the level of difficulty has good quality because 19 items (67.86%) are in the medium category, 2 items (7.14%) are in the difficult category, and 7 items (25%) are in the easy category; (4) Based on the differentiating power, it has good quality because 6 items (21.43%) are categorized as good, 21 items (75%) are categorized as quite good, and 1 item (3.75%) is categorized as poor; (5) Based on the effectiveness of the checkers, it has very good checker quality because 15 items (53.57%) with very good checkers, 9 items (32.14%) with good checkers, and 5 items (14.29%) with poor checkers.